2017
DOI: 10.1002/adma.201704551
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Flexible and Tough Layered Peptide Crystals

Abstract: One major challenge of functional material fabrication is combining flexibility, strength, and toughness. In several biological and artificial systems, these desired mechanical properties are achieved by hierarchical architectures and various forms of anisotropy, as found in bones and nacre. Here, it is reported that crystals of N-capped diphenylalanine, one of the most studied self-assembling systems in nanotechnology, exhibit well-ordered packing and diffraction of sub-Å resolution, yet display an exceptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…Before actuating properties of TS crystals can be explored as a platform for conversion of thermal energy to mechanical work, the range of their basic performance capabilities must be established based on commonly accepted performance indices. With exception of several special cases of organic materials with unusually high Young's moduli, organic crystals are generally known to be soft in nature, particularly when compared to metals and alloys. A large contribution to the mechanical properties of organic crystals is governed by intermolecular interactions, which are considerably weaker than the intramolecular (covalent) or metallic bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Before actuating properties of TS crystals can be explored as a platform for conversion of thermal energy to mechanical work, the range of their basic performance capabilities must be established based on commonly accepted performance indices. With exception of several special cases of organic materials with unusually high Young's moduli, organic crystals are generally known to be soft in nature, particularly when compared to metals and alloys. A large contribution to the mechanical properties of organic crystals is governed by intermolecular interactions, which are considerably weaker than the intramolecular (covalent) or metallic bonds.…”
Section: Discussionmentioning
confidence: 99%
“…The dosage-dependent MTT experiments showed that the cellular viabilities are all higher than 95%, even for the highest concentrations, implying that the nanobelts are not toxic and biocompatible to living organisms (Figure 6a). It can be accounted for the flexibility endowed by the laminated organization of the nanobelts, 45 which makes them deformable when interacting with the cells. Based on this positive result, we conducted the polarized imaging experiments in MCF-7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The large aspect ratio of those nanostructures implied that the growth kinetics preferred the axial direction. 35 The assemblies were examined further by powder X-ray diffraction (XRD). The diffraction peaks appeared at 5.8°, 11.2°, 17.1°, and 20.5°for 1-S assemblies (Figure 3d) and at 5.2°, 8.0°, 10.5°, 15.7°, and 26.3°for 2-R assemblies (Figure 3f), which could be attributable to the lattice spacing of the assemblies.…”
Section: -R 2-r and 3-r Showed Visible Suspended Solids Under An mentioning
confidence: 99%